Effectiveness and safety of topical sirolimus in children with angiofibromas and tuberous sclerosis complex - Andrea Fernández de Lara-Arrieta; Silvestre García-de La Puente; Janett Flores-Pérez; Carmen Flores-Pérez; Rodrigo Lomelí-Valdez; Andrea Venegas-Andrade; Carolina Palacios-López (Boletín Médico del Hospital Infantil de México)
Background: Tuberous sclerosis complex (TSC) is an autosomal dominant disease that can affect any organ with hamartomas. It is characterized by early-onset seizures and is associated with intellectual disability. The main dermatological findings include hypopigmented macules, shagreen patches, and angiofibromas, which appear in 81-96% of patients. Method: We conducted a quasi-experimental, before-and-after, open-label study in 10 patients with TSC and facial angiofibromas, aged 8-17 years, who were treated at the dermatology service of the Instituto Nacional de Pediatría in 2019 and 2020. All patients agreed to participate in the study and signed both consent and assent forms. All patients received treatment with 1% topical sirolimus for 6 months on the right side of the face, followed by 6 months on the left side of the face to assess recurrence. Each patient served as their own control. Measurements of baseline lesions were taken and followed monthly for 6 months. The changes in lesion size, measured in millimeters at each time point, were compared using repeated measures analysis of variance. Results: All children showed a decrease in the size and number of angiofibromas, as well as reduced erythema, from the 3rd month of treatment. Few recurrences were observed beginning at 4 months after discontinuation of the medication. Conclusion: Topical sirolimus is effective and safe for treating patients with angiofibromas and TSC.